Examining challenges and strategies in implementing STEM education in Malaysian secondary schools: perspectives of teachers and students / Muhammad Azli Riduan and Zarith Sofiah Othman - Riduan, Muhammad Azli; Othman, Zarith Sofiah (Universiti Teknologi MARA, Perlis, 2024)
This study examines the obstacles hindering the complete integration of STEM education in secondary schools, considering perspectives from both teachers and students, and proposing effective strategies. Employing a quantitative survey approach, the research involves 30 STEM teachers and 70 secondary school students. Findings demonstrate a consensus among participants, emphasizing issues such as inadequate teaching equipment and facilities as significant barriers to comprehensive STEM implementation. Educators favor technology-integrated teaching methods, while students show enthusiasm for incorporating these tools into their learning. Proposed effective strategies include enhancing internet accessibility and infrastructure. The study underscores the importance of engaging diverse stakeholders—teachers, parents, societal actors, and governmental bodies—to fully understand challenges and promote successful STEM integration in secondary education.